Analisis Pengaruh Karakteristik Perusahaan terhadap Perataan Laba oleh Perusahaan Manufaktur - Purba, Felino Pernando; Sinaga, Hotmaria; Munawarah, Munawarah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The purpose of this study is to test or analyze the accuracy of the Return On Assets, Firm Size, Current Ratio, Debt to Equity Ratio for Income Smoothing actions on corporate manufacturing published on the Stock Exchange in 2015-2017. In this study using the theories of financial statement analysis, financial management related to Return On Assets, Firm Size, Current Ratio, Debt to Equity Ratio. In this study using a quantitative observation process. In this observation also applies the process of observing data such as financial statements contained on the IDX website. This observation involved 153 corporate manufactures as a population, which each year experienced a profit in 2015-2017. The technique in citing samples in the observation, namely by using purposive sampling techniques so that 37 samples were multiplied for 3 years, 111 research samples were obtained. Simultaneous results with F test shows a significant effect on income smoothing, with the coefficient of determination test results of 4.2% so that the results of the research hypothesis Return On Assets, Firm Size, Current Ratio, Debt to Equity Ratio had no significant impact on income smoothing. And the T test produces a firm size variable that has a partial effect on income smoothing actions.